Analisis Nilai Ekonomi Substitusi Kangkung Air Afkir (Ipomoea Aquatica) Terfermentasi dalam Ransum Komersial Ayam Kampung Super Betina - Malo, Alfonsus I.; Dillak, Sutan Y. F. G.; Deno Ratu, Maria R.; Lole, Ulrikus R. (Yayasan Sumber Daya Manusia Cerdas, 2025)
The research objective was to analyze economic values of fermented water spinach (Ipomoea aquatic) as a substitution of commercial ration for super-female chickens. The research materials were 80 heads of super-female chickens at eight weeks old and the fermented water spinach that fermented by tape yeast. The research method used was an experiment applying a Completely Randomized Design comprise of 4 treatments and 5 replications. Each replication consists of 4 chickens. The treatments comprise R0: 100% of commercial ration; R1: 90% of commercial ration + 10% of water spinach fermented with tape yeast, R2: 80% of commercial ration + 20% of water spinach fermented with tape yeast, R3: 70% of commercial ration + 30% of water spinach fermented with tape yeast. The research variables were production cost, revenue, benefit, IOFC, B/C, R/C, BEP of production, and BEP of price. The results of the research show that the substitution of fermented water spinach in commercial feed for super female native chickens has the following economic performance: IOFC 240,035, R/C 1.81, B/C 0.81, production costs IDR 158,771, revenue IDR 287,739, income IDR 128,968, production BEP 1.98kg, and price BEP IDR 39,693/kg. In conclusion, the fermented water spinach as a substitution of commercial rations have significant effects (P<0.05) on all of the economic value indicators of the super-female chickens since the economic values were profitable and financially feasible.